The Analysis of Capacity Utilization Production as a Basis for Review Corporate Strategy According Islamic Economics - Asyik, Noor; Subroto, Athor; Izni Shafie, Dalili (Universitas Islam Negeri Raden Intan Lampung, 2023)
Capacity utilization is important in manufacturing strategies, especially in make-to-order manufacturing strategies. It is used to measure the best production achievements. The parameters for achieving the best production can be measured by reaching the break-even point, namely the point at which the costs are equal to income. In 2022 the capacity utilization production of PT XYZ which is a precast concrete industrial corporation in Indonesia is 73.40% and under the break-even point. Achieving utilization above the break-even point is a competitive advantage for the corporation. This research was conducted to examine the company's current strategy to provide suggestions for formulating corporate management strategies according to Islamic economics with the analysis of capacity utilization production. Meanwhile, the research sample was conducted and analyzed from 2015 to 2026. The method used in this research is quantitative descriptive research, analysis using different statistical tests to analyze capacity utilization, and qualitative descriptive analysis methods to observe corporate strategy. The analysis found that the capacity utilization level in 2016 and 2017 and the prognosis for 2023 exceeded the break-even point. However, from 2024 to 2026, the results of the capacity utilization level will be below the break-even point. So, it is necessary to consider strategy formulation to avoid losses. Some of the suggestions for formulating corporate strategies result are diversification of business unit strategies into the construction sector, corporate synergy, partnerships with strategic partners, and market penetration according to Islamic economics.